Pelatihan Menyelesaikan Soal-Soal Ujian Masuk PTN Dan Sekolah Kedinasan Melalui Trik 3M di Kabupaten Jayapura - Mokere, Ruth Megawati (MALLOMO: Journal of Community Service, 2021)
The selection of the new student in university is like specter for most hight school students who will continue their education to college. One of the causes is because the lack of students’ readiness, as well as the selection techniques that have selective screening criteria. Which the test is carried out through CAT (Computer Assisted Test) with the provisions of passing Grade. This is the reason for carrying out this service. Namely training to high school student specially for students at GKI Yoanibi Doyo Baru, in Jayapura Regency, in preparing themselves to join the selection. This training is carried out for a week with a meeting duration of 2 hours every day. Through practicing to solve the questions with 3M tricks (menganalisis / analyzing, menentukan / determining, and mengerjakan / doing). The result is their knowledge are increased and ready for compete the selection. Furthermore, we are suggested to collaborate with other fields of course in providing acomplete materials.